2001
DOI: 10.1111/j.1559-1816.2001.tb02481.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Decision Making by Means of Dissent1

Abstract: Antidotes to problems associated with uniformity of viewpoints have generally involved dissent in one form or another (Katzenstein, 1996), one being “devil's advocate.” Research on authentic dissent has documented additional advantages in that it stimulates divergent and original thought (Nemeth, 1995). In this study, authentic disscnt was compared with devil's advocate and with no dissent. Findings indicate that authentic dissent was superior in (a) stimulating a greater proportion of original thoughts, (b) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 30 publications
0
67
0
Order By: Relevance
“…They have also suggested that voice is especially important in the context of work groups . Because groups are characterized by interdependence, shared responsibility, diffuse expertise, and divergent perspectives, their effectiveness depends on members sharing knowledge and speaking up with suggestions and opinions (Mesmer-Magnus & DeChurch, 2009;Nemeth, Connell, Rogers, & Brown, 2001). However, as many researchers have argued, group members often do not share their opinions, ideas, and concerns, and such an absence of voice can have serious negative implications for group performance (e.g., Argyris, 1991;Janis, 1972;Perlow & Williams, 2003).…”
mentioning
confidence: 99%
“…They have also suggested that voice is especially important in the context of work groups . Because groups are characterized by interdependence, shared responsibility, diffuse expertise, and divergent perspectives, their effectiveness depends on members sharing knowledge and speaking up with suggestions and opinions (Mesmer-Magnus & DeChurch, 2009;Nemeth, Connell, Rogers, & Brown, 2001). However, as many researchers have argued, group members often do not share their opinions, ideas, and concerns, and such an absence of voice can have serious negative implications for group performance (e.g., Argyris, 1991;Janis, 1972;Perlow & Williams, 2003).…”
mentioning
confidence: 99%
“…Nor do we mean techniques by which debate is role played, as with devil's advocate. In fact, we have evidence that such role-playing techniques do not stimulate creative thought and solutions as does authentic dissent (Nemeth, Connell, Rogers, & Brown, 2001;). What we are arguing is that authentic differences stimulate thought that encourages the consideration of more information, more strategies and creative solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many discussions of voice and related constructs often assume that voice is public, rather than private. For example, research suggests that dissent expressed in groups facilitates more in-depth discussions, thus increasing decision quality (Nemeth, Connell, Rogers, & Brown, 2001) and innovation (De Dreu & West, 2001a). In contrast, private dissent is often considered inefficient because of the need to organize additional meetings with relevant stakeholders (Eden & Long, 2014).…”
Section: Introductionmentioning
confidence: 99%